2024
DOI: 10.1002/anie.202318856
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Symmetry Breaking of Achiral Molecules Leading to the Formation of Homochiral Superstructures that Exhibit Mechanoluminescence

Zheng‐Fei Liu,
Xin‐Yi Ye,
Lihua Chen
et al.

Abstract: Chirality, with its intrinsic symmetry‐breaking feature, is frequently utilized in the creation of acentric crystalline functional materials that exhibit intriguing optoelectronic properties. On the other hand, the development of chiral crystals from achiral molecules offers a solution that bypasses the need for enantiopure motifs, presenting a promising alternative and thereby expanding the possibilities of the self‐assembly toolkit. Nevertheless, the rational design of achiral molecules that prefer spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…A large number of hexafluoroacetylacetonate (hfa), dibenzoylmethide (dbm), thenoyl-trifluoroacetonate (tta), and other chelates with capping/bridging ligands have been demonstrated to be ML active. 29 ML and PL spectral profiles are generally reported to be "similar"; thus, ML is expected to 106 (Z)-BFBM-TPE, 170 CDpP-G/B, 171 BCPC, 172 TXENE-Y, 154 1a, 173 ImBr, 174 FCO-CzS, 141 XPy, 148 TPA-o-3COOMe, 175 [Sm(dbm) 4 ]TEA, 176 [Eu(tta) 3 (phen)], 177 [Ru(bpy) 3 ]Cl 2 , 178 PL intensity contrast in a homometallic complex, 130 which was explained by the characteristic direct-lanthanide(III) excitation process in ML (denoted as the "f-f priority rule" in contrast to ligand-excitation in PL). 51 The number of studies reporting the chromic shifts in ML of organic molecules relative to their PL is also increasing, similar to those observed in MRL (PL in ground forms), as depicted by the blue and red shades in Figure 4.…”
Section: Molecular Design For MLmentioning
confidence: 95%
See 4 more Smart Citations
“…A large number of hexafluoroacetylacetonate (hfa), dibenzoylmethide (dbm), thenoyl-trifluoroacetonate (tta), and other chelates with capping/bridging ligands have been demonstrated to be ML active. 29 ML and PL spectral profiles are generally reported to be "similar"; thus, ML is expected to 106 (Z)-BFBM-TPE, 170 CDpP-G/B, 171 BCPC, 172 TXENE-Y, 154 1a, 173 ImBr, 174 FCO-CzS, 141 XPy, 148 TPA-o-3COOMe, 175 [Sm(dbm) 4 ]TEA, 176 [Eu(tta) 3 (phen)], 177 [Ru(bpy) 3 ]Cl 2 , 178 PL intensity contrast in a homometallic complex, 130 which was explained by the characteristic direct-lanthanide(III) excitation process in ML (denoted as the "f-f priority rule" in contrast to ligand-excitation in PL). 51 The number of studies reporting the chromic shifts in ML of organic molecules relative to their PL is also increasing, similar to those observed in MRL (PL in ground forms), as depicted by the blue and red shades in Figure 4.…”
Section: Molecular Design For MLmentioning
confidence: 95%
“…132 Indeed, Yang et al recently demonstrated the critical role of polarity in molecular ML activity by comparing spontaneously polarized and nonpolarized crystalline phases (see section 3.5). 148 Lanthanide(III) coordination complexes are considered as promising candidates for ML-active materials, unlike MRL (Figure 4). A large number of hexafluoroacetylacetonate (hfa), dibenzoylmethide (dbm), thenoyl-trifluoroacetonate (tta), and other chelates with capping/bridging ligands have been demonstrated to be ML active.…”
Section: Molecular Design For MLmentioning
confidence: 99%
See 3 more Smart Citations